Phylogenetic affiliation of endophytic actinobacteria associated with red gum tree grown in salinity area and their plant growth promoting properties and suppression of phytopathogens, and genome data mining of selected strains - Kaewkla, Onuma; Kiakhunthod, Kawintip; Chookhampaeng, Sumalee; Klinjantasorm, Busayarat; Klankeo, Piriya; Dungkaew, Winya (Frontiers in Plant Science, 2025)
Eucalyptus is an economic plant of Thailand that can tolerate salt and drought stress. This work aims to report on the study of biodiversity among endophytic actinobacteria isolated from Eucalyptus camaldulensis grown in saline soil, as well as their properties for promoting plant growth and inhibiting fungal pathogens in vitro. Root, twig, and leaf samples of five plants, E. camaldulensis grown in Kalasin Province, Thailand, were collected. The soil samples of each plant were collected, and soil salinity was evaluated by the electrical conductivity of a saturated soil extract (ECe). It was found that the ECe of the soil was between 4.5 and 12 dS/m, and the pH of the soil ranged between 3.9 and 5.2. Based on their morphology and 16S rRNA gene sequences, the majority of the isolates (552, 96.7%) were identified as the genus Streptomyces. The remaining isolates (19, 3.3%), which included ten genera: Cellulosimicrobium (3), Kocuria (3), Brevibacterium (2), Micrococcus (2), Microbacterium (2), Peterkaempfera (2), Tsukamurella (2), Brachybacterium (1), Curtobacterium (1), and Gordonia (1). Two hundred and seventy-three isolates were tested for antifungal activity against two eucalyptus pathogens, Pseudoplagiostroma eucalypti LS6 and Cladosporium sp. LB1. Most isolates showed antifungal activity against P. eucalypti LS6. The plant growth-promoting (PGP) study of 154 selected strains showed that 154 (100%), 18 (11.7%), 14 (9.1%), and 7 (4.5%) isolates could produce indole-3-acetic acid (IAA), 1-aminocyclopropane (ACC) deaminase, solubilize phosphate, and fix nitrogen in vitro, respectively. Identification of non-actinobacteria isolates based on 16S rRNA gene sequence analysis indicated that 10 genera were obtained: Aureimonas, Bacillus, Chryseobacterium, Deinococcus, Massilia, Methylobacterium, Pseudomonas, Serratia, Staphylococcus, and Stenotrophomonas. One selected Streptomyces strain, EWL5.1, was selected for a seed germination test in salinity stress and PGP in planta. The result indicated that this strain could support the seedling length vigor index (SLVI) of eucalyptus seedlings in salinity conditions and significantly increase the fresh weight of eucalyptus seedlings in planta. Four representative Streptomyces strains and one strain of Micrococcus were sequenced for their genomes. The result indicated that these four Streptomyces strains comprise various biosynthesis gene clusters (BGCs) of antibiotic production. Genome data mining also reveals that all strains contain genes encoding PGP properties. These potential strains can be applied to be used as PGPB to support eucalyptus growth in the future.